Deletion of Apoptosis Inhibitor of Macrophage (AIM)/CD5L Attenuates the Inflammatory Response and Infarct Size in Acute Myocardial Infarction. Issue 4 (April 2016) - Nishikido, Toshiyuki; Oyama, Jun‐ichi; Shiraki, Aya; Komoda, Hiroshi; Node, Koichi
Abstract : Background: An excessive inflammatory response after myocardial infarction (MI) increases myocardial injury. The toll‐like receptor (TLR)‐4 is activated by the recognition of endogenous ligands and is proinflammatory when there is myocardial tissue injury. The apoptosis inhibitor of the macrophage (AIM) is known to provoke an efflux of saturated free fatty acids (FFA) due to lipolysis, which causes inflammation via the TLR‐4 pathway. Therefore, this study investigated the hypothesis that AIM causes a proinflammatory response after MI. Methods and Results: The left anterior descending coronary artery was ligated to induce MI in both AIM‐knockout (AIM −/− ) and wild‐type (WT) mice. After 3 days, the inflammatory response from activation of the TLR‐4/NFκB pathway was assessed, and infarct size was measured by staining with triphenyltetrazolium chloride. In addition, left ventricular remodeling was examined after 28 days. Although the area at risk was similar between AIM −/− and WT mice, the infarct size was significantly smaller in AIM −/− mice ( P =0.02). The heart weight–to–body weight ratio and myocardial fibrosis were also decreased in the AIM −/− mice, and the 28‐day survival rate was improved ( P <0.01). With the reduction of plasma FFA in AIM −/− mice, myocardial IRAK4 and NFκB activity were decreased (all P <0.05). Moreover, there was a reduction in myeloperoxidase activity and inducible nitric oxide synthase as part of the inflammatory response ( P <0.01, P =0.03, respectively). Furthermore, NFκB DNA‐binding activation via TLR‐4, neutrophil infiltration, and inflammatory mediators were decreased in AIM −/− mice. Conclusions: The deletion of AIM reduced the inflammatory response and infarct size and improved survival after myocardial infarction.